2002
DOI: 10.1097/01.lab.0000036874.83540.2b
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Epidermal Barrier Function by Photoacoustic Spectrometry in Relation to Its Importance in the Pathogenesis of Atopic Dermatitis

Abstract: SUMMARY:With the use of the photoacoustic spectrometry system, in which a mixture of lipid-and water-soluble dyes is applied to the skin and then irradiated with light from a xenon lamp (425 nm and 550 nm), we measured photoacoustic signals of both dyes within the stratum corneum and their disappearance rate through the stratum corneum. The signal intensity was higher and dyes penetrated faster in clinically normal skin of patients with atopic dermatitis (AD) compared with healthy subjects, indicating an impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…It is interesting that these differences in ceramides and sphingoid bases usually correlated with epidermal barrier dysregulation were observed in nonlesional skin from subjects with unflared AD, given that an impaired epidermal barrier in AD is usually associated with active lesions or nonlesional skin adjacent to active lesions (47). Therefore, the sweat mediator lipidome appears to indicate a sustained biochemical dysregulation in subjects with AD and may provide an opportunity for preclinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that these differences in ceramides and sphingoid bases usually correlated with epidermal barrier dysregulation were observed in nonlesional skin from subjects with unflared AD, given that an impaired epidermal barrier in AD is usually associated with active lesions or nonlesional skin adjacent to active lesions (47). Therefore, the sweat mediator lipidome appears to indicate a sustained biochemical dysregulation in subjects with AD and may provide an opportunity for preclinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…The defect of the barrier function in nonlesional skin of AD patients has been generally evidenced by increased transepidermal water loss (TEWL) measured with an evaporimeter (which evaluates the evaporation rate of water through the skin) [6] . Also, using photoacoustic spectrometry, we demonstrated the signifi cantly enhanced penetration rate of chemicals in nonlesional skin of AD patients compared with healthy skin [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The clinically normal, noninfl ammatory, but dry and scaly nonlesional skin of AD patients seems to play a key role in the continued recurrence of the dermatitis because the cutaneous barrier function in nonlesional skin is generally impaired at a level similar to that in lesional skin [4,5] . Thus, AD is considered a barrier disease in which antigens and irritants that can easily penetrate nonlesional skin trigger and worsen the dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Moreover, previous studies have reported that the long lamellar structure plays an important role in mediating the barrier function of intercellular lipids in the stratum corneum. [21][22][23] In order to extrapolate the effects of l-menthol on barrier function, we focused on changes in the long lamellar structure. We analyzed the long lamellar structures and determined the integrated intensity, lamellar distance, and half-width at half maximum (Fig.…”
Section: Resultsmentioning
confidence: 99%